Survival after minimally invasive vs. open radical nephrectomy for stage I and II renal cell carcinoma - Dursun, Furkan; Elshabrawy, Ahmed; Wang, Hanzhang; Rodriguez, Ronald; Liss, Michael A.; Kaushik, Dharam; Gelfond, Jonathan; Mansour, Ahmed M. (International journal of clinical oncology, 2022)
Background A recently reported phase III randomized trial comparing open and minimally invasive hysterectomy showed significantly higher rates of local recurrence after minimally invasive surgery (MIS) for cervical cancer. This raised concerns regarding patterns of recurrences and survival after MIS in general. This study aims to determine the effect of MIS on all-cause mortality among patients undergoing radical nephrectomy for Stage I and II renal cell carcinoma (RCC). Methods We utilized the National Cancer Database to identify patients diagnosed with clinical stage I–II RCCs between 2010 and 2013. Patients for whom a laparoscopic or robotic radical nephrectomy was attempted were compared to patients who underwent open radical nephrectomy (ORN). Adjusted regression models with inverse probability propensity score weighting (IPW) were utilized to identify independent predictors of receiving MIS. All-cause mortality rates were compared using IPW survival functions and log-rank tests. Adjusted Cox proportional hazard models were fitted to determine independent predictors of OS. Results 27,642 patients were identified; 11,524 (41.7%) had MIS, while 16,118 (58.3%) had ORN. Kaplan–Meier survival curves in the IPW cohort showed significant OS advantage for patients who underwent MIS ( p < 0.001). Furthermore, length of hospital stays (3 vs. 4 days), 30 day readmission rates (2.4 vs. 2.87%), 30 day (0.53 vs. 0.96%) and 90 day mortality rates (1.04 vs. 1.77%) were significantly higher in the ORN group ( p < 0.001). Conclusions MIS was associated with better OS outcomes compared to ORN for stage I and II RCC. In addition, MIS had lower post-operative readmission, 30- and 90 day mortality rates.